Analysis and improvement of the efficiency of frequency converters with pulse width modulation - Bogdan Vasilev (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In order to identify the best control algorithm, the effects of modulation control algorithms on the energy characteristics of a two-level autonomous frequency converter inverter were studied. The research was carried out by the methods of mathematical and simulation modeling. The equa-tions of mathematical description were compiled taking into account a number of generally accepted assumptions. An equivalent circuit of a two-level autonomous inverter was created. Comparisons of pulse-width modulation algorithms with carrier signals of various shapes and frequencies were made. Three different forms of carrier signal were used: triangular, sawtooth with a falling edge and sawtooth with a leading edge. Studies were conducted at frequencies of 3,000, 6,000 and 9,000 Hz. Conclusions were made about the identity of the spectral composition of the front and rear edges of the sawtooth signal, it was also noted that with the triangular waveform, being the part of the har-monics, present in the sawtooth form is removed, so, the triangular shape provides the best result of the autonomous inverter. Also, by increasing in the carrier frequency, it was noted that pulse packets appear at different harmonic numbers, shift, and the amplitude and distortion factor decrease, that means, the best performance was obtained at the maximum frequency studied. In the study of the voltage at the output of the chokes at different frequencies of the carrier signal, it was noted that at a higher frequency, the ripple of the output voltage decreases. Throttles do not eliminate harmonics, but only reduce their amplitude. Based on the results, it was concluded that the algorithm with a triangular carrier signal and the maximum frequency provides the best harmonic composition of the output voltage of the frequency converter.